Research and Development of Civil Engineering Intelligent Structure System - Junkai Xie; Bo Gao; Huamin Cheng (Advances in Civil Engineering)
With the rapid development of global civil engineering construction, the intelligent structural system of civil engineering has evolved into one of the current global frontier disciplines. The research on the intelligent structural system of civil engineering and the current development situation are analyzed, and the main problems are combined. Giving reasonable suggestions is of great significance to the country's vigorous development of civil engineering intelligent structure system. This paper designs a new type of three-dimensional fiber grating sensor, including the design of the matrix model and the design of fiber grating strain gauges. This new sensor can effectively measure three-dimensional space, greatly expanding the application range of fiber grating sensors. In this paper, the design lighting area of each light pipe is taken as a unit. Each unit is set with 4 measuring points at the center and the edge. Each measuring point reads 3 illuminance value parameters and records the average value. Based on the results and comprehensive consideration of the short board situation, the research conclusions and recommendations are put forward. The foundation wall with aerated concrete blocks as the wall material can meet the requirements of 50% energy saving for exterior wall buildings with external decoration and internal insulation mortar. Compared with the benchmark wall of 50% energy saving of external wall buildings, the heat transfer coefficient is reduced by 50.1%, and the actual energy-saving effect of the wall can reach 75%. Meet the requirements of 65% for the energy-saving effect of exterior wall buildings. This paper considers economic parameters, such as the investment cost of building insulation materials, energy-saving income, and investment recovery period, and establishes a calculation model for analyzing the economics of insulation materials. Based on the heat transfer model of the composite wall and the fuel energy combustion equation, greenhouse gas is an established calculation model for CO2 and SO2 emissions. Studies have shown that when considering the room temperature insulation performance of insulation materials, the time required for the side of the concrete slab with glass fiber felt and aerogel insulation materials is about 2022 and 3363 s, respectively, indicating the fire resistance of aerogel insulation materials significantly better than fiberglass.